Rapid Gene Turnover as a Significant Source of Genetic Variation in a Recently Seeded Population of a Healthcare-Associated Pathogen - Graña-Miraglia, Lucía; Lozano, Luis F.; Velázquez, Consuelo; Volkow-Fernández, Patricia; Pérez-Oseguera, Ángeles; Cevallos, Miguel A.; Castillo-Ramírez, Santiago (Frontiers in Microbiology, 2017)
Genome sequencing has been useful to gain an understanding of bacterial evolution. It has been used for studying the phylogeography and/or the impact of mutation and recombination on bacterial populations. However, it has rarely been used to study gene turnover at microevolutionary scales. Here, we sequenced Mexican strains of the human pathogen Acinetobacter baumannii sampled from the same locale over a 3 year period to obtain insights into the microevolutionary dynamics of gene content variability. We found that the Mexican A. baumannii population was recently founded and has been emerging due to a rapid clonal expansion. Furthermore, we noticed that on average the Mexican strains differed from each other by over 300 genes and, notably, this gene content variation has accrued more frequently and faster than the accumulation of mutations. Moreover, due to its rapid pace, gene content variation reflects the phylogeny only at very short periods of time. Additionally, we found that the external branches of the phylogeny had almost 100 more genes than the internal branches. All in all, these results show that rapid gene turnover has been of paramount importance in producing genetic variation within this population and demonstrate the utility of genome sequencing to study alternative forms of genetic variation.